A hierarchical analysis of the latent trait of borderline personality disorder and its possible clinical implications. (June 2020) - Dreyße, Kathrin; Beller, Johannes; Armbrust, Michael; Kröger, Christoph
Highlights: There is a hierarchical scale within the impulsivity & emotion dysregulation scale The hierarchical analysis of borderline-symptoms reveals findings to the latent trait Emotion dysregulation seems to be the core feature of borderline The acute risk of a person with the borderline disorder can be estimate faster First needed steps of treatment can be planned more specifically Abstract: Borderline personality disorder (BPD) is a severe mental disorder which is accompanied by impaired functioning, complex psychosocial problems and incurs large costs. However, it rarely has been examined whether BPD symptoms form a hierarchical (Mokken) scale, which would imply that symptoms are ordered along a latent dimension of borderline severity. In this study the data from 1, 198 inpatients of a psychosomatic clinic were examined. A non-parametric Mokken analysis was employed to investigate if the BPD symptoms measured by the impulsivity and emotion dysregulation scale (IES-27) formed a hierarchical scale. 16 of the 27 items, mainly regarding emotion dysregulation, formed a monotonous Mokken scale with a very strong hierarchy of BPD symptoms. These results imply that single BPD symptoms provide information about BPD severity, suggesting several important consequences regarding escalation of BPD, diagnosis and treatment, e.g. how to optimize treatment planning.